Changes in growth, photosynthesis and chlorophyll fluorescence in the freshwater dinoflagellate Peridinium umbonatum (Peridiniales, Pyrrophyta) in response to different temperatures. Issue 4 (1st July 2016) - Xu, Jinzhu; Wu, XingHua; Yang, Yanjun; Xu, Sha; Kang, Yuanhao; Fu, Xiaoli; Yue, Hong; Shi, Junqiong; Wu, Zhongxing
Abstract: Peridinium umbonatum causes harmful algal blooms in freshwater ecosystems; however, environmental conditions that promote accelerated growth and blooming of this organism have not been resolved. Increasing global temperatures has been suggested as a possible factor for shifts in phytoplankton composition to more harmful species. Therefore, this study investigated the physiological responses of this freshwater dinoflagellate to different temperatures, a factor that will strongly be affected by future climate change scenarios. Specific growth rates of P. umbonatum were markedly lower at 10°C and 14°C than at 18°C, 25°C and 30°C, with the highest growth rate measured at 18°C. Cell mobility was significantly inhibited at 10°C and 14°C. The maximum photochemical efficiency ( F v / F m ) of photosystem II and maximum relative electron transport rate decreased significantly at temperatures below 14°C. However, nonphotochemical quenching significantly increased at 10°C and 14°C. Variable fluorescence at phase J increased in chlorophyll a fluorescence transients for P. umbonatum grown at 10°C and 14°C. The density of reaction centres and quantum energy flux ratios increased with increasing temperature, whereas the absorption and trapping energy flux, as well as the relative variable fluorescence intensity at the J-step, decreased with increasing temperature. These results suggest that low temperatures inhibit photosynthesis in P. umbonatum, resulting in low specific growth rates and increased cell immobility. This finding suggests that exposure to a temperature of 18°C plays an important role in the growth and cyst germination of Peridinium, implying that increasing temperature might promote dinoflagellate Peridinium blooms.